Korsakoff's Syndrome and Modern German Literature: Alfred Döblin's Medical Dissertation - Roland Dollinger (Studies in 20th & 21st Century Literature, 1998)
This essay deals with the historical and cultural interrelationships between the medical and psychiatric discourses on memory and memory disorders at the end of the nineteenth century and the invention of an abstract and highly dissociated literary style in modern German literature. An historical reading of Alfred Döblin's medical dissertation (1905) on Korsakoff's syndrome, an amnestic disorder, shows the confluence of both his psychiatric and aesthetic interests in human memory and its failures. The essay analyzes Döblin's medical dissertation less as the contribution of a young psychiatrist to his discipline but rather as an historical text that challenges us to see where some of the medical and aesthetic concerns of early twentieth-century German culture meet.
Keywords: historical; cultural; interrelationship; medical; psychiatric; discourse; memory; memory disorders; nineteenth century; invention; dissociated literary style; modern German literature; German; Alfred Döblin; historical reading; medical dissertation; Korsakoff& #x27; s syndrome; amnestic disorder; aesthetic interest; human memory; failure; early twentieth-century German culture